The fair-minded rich and healthy? (Youth) unemployment, inequality and fairness concerns in preferences for redistribution - Stephanie Armbruster (University of Basel, Center of Business and Economics (WWZ), 2020)
Do rising inequality and youth unemployment aect preferences for redistribution? Using country-level European survey data from 2002 to 2015, I show that changes in market inequality and the rise of (youth) unemployment increase preferences for redistribution. The ndings are supported by the respondents' fairness concerns. Estimated effects exhibit substantial heterogeneity. There is systematic variation among fairness concerns with respect to income and health, which are triggered by market income inequality and (youth) unemployment. The preferences of the relatively rich and healthy are more responsive to the level of inequality and youth unemployment. At very high youth unemployment rates, even the rich might be in favor of redistribution. Results suggest that "income-and health-dependent fairness concerns" exist.
Keywords: A13; D10; D31; D63; H23; C3; 330; Preferences for redistribution; Inequality; Fairness concerns; Income-dependent altruism; Health-dependent-altruism; Youth unemployment; unemployment; Meltzer-Richards; Inequality; Market inequality